Could electrohysterography be the solution for external uterine monitoring in obese women?. (May 2018) - Vlemminx, Marion; Thijssen, Kirsten; Bajlekov, Galin; Dieleman, Jeanne; Van Der Hout-Van Der Jagt, M.; Oei, S.
Abstract Objective To evaluate the influence of maternal obesity on the performance of external tocodynamometry and electrohysterography. Study design In a 2-hour measurement during term labor, uterine contractions were simultaneously measured by electrohysterography, external tocodynamometry, and intra-uterine pressure catheter. The sensitivity was compared between groups based on obesity (non-obese/obese/morbidly obese) or uterine palpation (good/moderate/poor), and was correlated to maternal BMI and abdominal circumference. Result We included 14 morbidly obese, 18 obese, and 20 non-obese women. In morbidly obese women, the median sensitivity was 87.2% (IQR 74–93) by electrohysterography and 45.0% (IQR 36–66) by external tocodynamometry (p  < 0.001). The sensitivity of electrohysterography appeared to be non-influenced by obesity category (p  = 0.279) and uterine palpation (p  = 0.451), while the sensitivity of tocodynamometry decreased significantly (p  = 0.005 andp  < 0.001, respectively). Furthermore, the sensitivity of both external methods was negatively correlated with obesity parameters, being non-significant for electrohysterography (rangep- values 0.057–0.088) and significant for external tocodynamometry (allp -values < 0.001). Conclusions Electrohysterography performs significantly better than external tocodynamometry in case of maternal obesity.